On the Strategy of Integrated Water Resources Management in Kazakhstan - MYRZAHMETOV, Menlibay; UMBETOVA, Sholpan M.; ASHIRYAYEV, Klim Sh.; KOZHAKHAN, Aigul K.; KANARBAY, Asel U. (Journal of Environmental Management and Tourism, 2019)
The article outlines the concept and presents some proposals for the implementation of the integrated water resources management strategy of the Republic of Kazakhstan. The purpose of the article is to analyze the strategy of integrated water resources management in Kazakhstan. In particular, the principles for achieving a qualitatively new state of the water sector, the main components of the state water policy at the current stage, the main mechanisms for its implementation and the stages of implementation are indicated. The novelty of this article lies in the fact that the integrated water resources management at the current stage has been analyzed, and it will be interesting for other countries.